The effect of daytime and nighttime temperature on the cover colour of fruits in an apple gene bank - Lakatos, László; Szabó, Tibor; Racskó, József; Szabó, Zoltán; Soltész, Miklós; Nyéki, József (Acta Agraria Debreceniensis, 2005)
Skin colour of fruits is an important fruit quality parameter. Fruit growers know the phenomenon that the apple colouration is very good in one year while in other years the green and red apples can be differentiated only on the basis of the morphological characteristics of the fruits. There are great differences in values of cover colour between years.In the first step, the relationships between day and night temperature, the difference between day and night temperature and fruit skin colour should be determined. In this study, the authors investigate and quantify this relationship.